Current diagnosis & treatment critical care - Bongard, Fred S. (Lange medial book., 2008)
Equips practitioners and residents with coverage of the salient elements of diagnosis and treatment of critically ill patients. The Second Edition features new material on acute respiratory distress syndrome, nutrition, prevention of bleeding, respiratory failure, fluid & electrolyte disorders, critical care monitoring, and imaging procedures. - Publisher.